2016
DOI: 10.1161/circgenetics.115.001218
|View full text |Cite
|
Sign up to set email alerts
|

Do Genetic Factors Modify the Relationship Between Obesity and Hypertriglyceridemia?

Abstract: M ore than 600 million people are estimated to be obese worldwide, 1 which is thought to be primarily a consequence of lifestyles characterized by consumption of energy-dense foods with poor nutritional content and lack of physical activity in the workplace and at home. The high prevalence of obesity is of considerable concern owing to the plethora of its life-threatening sequelae, including type 2 diabetes mellitus, coronary heart disease, and cerebrovascular disease.2 Accumulation of triglycerides in adipose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 38 publications
5
9
0
Order By: Relevance
“…It would be of interest to follow-up on this suggestive finding in a larger cohort and preferentially with objectively measured physical activity. Also of notice, it has recently been suggested that the interaction between the triglyceride wGRS and BMI is stronger in women (17). In the present study, we confirm this observation also for the interaction between the wGRS and HOMA-IR.…”
Section: Interactionssupporting
confidence: 91%
See 4 more Smart Citations
“…It would be of interest to follow-up on this suggestive finding in a larger cohort and preferentially with objectively measured physical activity. Also of notice, it has recently been suggested that the interaction between the triglyceride wGRS and BMI is stronger in women (17). In the present study, we confirm this observation also for the interaction between the wGRS and HOMA-IR.…”
Section: Interactionssupporting
confidence: 91%
“…Previous studies of interactions in cross-sectional settings have found comparable interactions suggesting a stronger association between the wGRS and triglycerides in obese or in more insulin-resistant individuals (14)(15)(16)(17)19). In this study, we demonstrate that the interaction with HOMA-IR is also evident in a prospective setting consolidating the results from previous studies using cross-sectional data.…”
Section: Interactionssupporting
confidence: 86%
See 3 more Smart Citations